Variations of nuclear DNA content of Musa (AAA) CV. Williams micropropagated in high concentration of N6-benzyladenine - Giménez Alvarado, Carlos; Colmenares Esqueda, Maribel (Ciencia, 1970)
Shepherd and Dos Santos (1) had reported that the Musa plants micropropagated with N6-benzyladenine (BA) show higher percentage of mitotic abnormalities than plants propagated by classical methods. In this research, adventitious shoots of Williams (AAA), obtained by induction in 20 mg/L BA, were characterized with flow cytometry. Nuclei were isolated from banana leaves and stained using propidium iodine (50 Âµg/L). The distribution of the relative nuclear DNA content of these in vitro plants was according to the following intervals: 8% between 3 to 3.25, 27% 3.25 to 3.5, 38% 3.5 to 3.75, 23% 3.75 to 4 and 4% 4.25 to 4.5. These results show the possibilities to obtain somaclones with different nuclear DNA contents from triploid cultivar for Musa improvements programs.